Fostering Inclusive Mathematics Learning: A Lesson Study Approach Integrating the Wordwall Digital Platform for Special Needs Students - Nia Wahyu Damayanti; Ali Carli (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2026)
This study investigated the integration of the Wordwall digital interactive learning platform into a Lesson Study framework to enhance mathematics instruction for students with special needs. Conducted at a Special Education School (SLB), the research explored digital tools and collaborative teacher development improved student engagement, conceptual understanding, and motivation in learning basic mathematical concepts. A group of mathematics teachers participated in  lesson planning, classroom implementation, observation, and reflection, during which Wordwall was used to design interactive and accessible math activities tailored to students with diverse disabilities. Despite growing interest in inclusive education, few studies had examined how structured professional development models such as Lesson Study could be effectively integrated with digital platforms like Wordwall in special education contexts. This study addressed that gap by demonstrating that the strategic integration of these tools significantly enhanced students’ active participation and conceptual comprehension. The interactive features of Wordwall supported multisensory engagement and differentiated instruction, while the Lesson Study process facilitated sustained collaboration and adaptive teaching among educators. The findings suggest that integrating technology-enhanced learning with professional learning communities not only improved students’ outcomes, such as accuracy in basic computations, mathematical reasoning, and enthusiasm but also strengthened teachers' capacities in inclusive instructional design, reflective practice, and adaptive pedagogical strategies. These results showed insights for future research and practice, especially in developing inclusive models that digital technology and collaborative teaching to promote equity and quality in special education.